Jef van Bilsen, de onafhankelijkheid van Congo en de visie op Lumumba - Beke, Dirk (Afrika Focus, 2000)
This article gives an overview of the involvement of Professor Jef Van Bilsen in Belgian politics before and during the Second World War and during the decolonisation of the Belgian Congo. It is based mainly on the statements and writings of Van Bilsen himself and on interviews with him. These personal testimonies are complemented with brief comments from others on Van Bilsen. Van Bilsen's political career reveals a unique and interesting evolution. Before the Second World War, he became active in the Flemish emancipation struggle. As a student and young lawyer, he was a leading member of the elitist right wing movement, Verdinaso, which strove for the unification of Belgium and the Netherlands. During the war, he joined, together with a group ofVerdinaso members, the royalist armed resistance against the German occupation. Immediately after the war, his commitment and his personal contacts allowed him to become a journalist in Central Africa, where he was brought face to face with the narrow-minded Belgian colonial policy and where he forged contacts with the first Congolese nationalists. In the early fifties, Van Bilsen returned to Belgium, where he became a professor in colonial and development matters and started advocating the planning of an independence process for the Belgian colonies in a political and academic environment that was very hostile to any idea of decolonisation. When the Belgian government in 1960, under internal and international pressure, was obliged to grant independence, we see Van Bilsen offering his services as an adviser to the Congolese nationalists. During the independence talks and immediately after independence, the first President, Kasavubu, recruited him as a personal adviser. Van Bilsen declared in later interviews that he tried to act as a neutral adviser. During the conflict between President Kasavubu, Prime Minister Lumumba and the Katangese leader Tshombe, he strove for reconciliation between the three opponents and for a UN-sponsored political compromise. He strongly condemned Belgian support for the secession of Katanga. Although Van Bilsen declared himself to be personally sympathetic to Lumumba, he was accused openly by Lumumba of defending Belgian and western interests. Finally, Van Bilsen was forced to leave the Congo but he continued to advocate an agreement between Kasavubu, Lumumba and Tshombe. In New York at the UN-sessions on the Congo-crisis, he argued forcefully for a resolute commitment to this policy on the part of the UN and that Belgium take a back seat in Congolese politics. In his later career as professor and as founder of the Belgian Overseas Co-operation Service, Van Bilsen became a determined defender of unconditional co-operation, a co-operation which was not tied to the economic and financial interests of western donors. He also continued to stress fervently the importance of the UN for the development of the Third World. The overview of Van Bilsen's political career reveals the role that personal networks can play in contacts, even in circles whose members find themselves in opposing camps. It also shows how Van Bilsen's confrontation with the colonial and post-colonial situation in Central Afrika led him to insist on the formation of an African elite which was committed to political and social emancipation. KEY WORDS: Belgian recent history, Belgian Congo, Congo's independence, Lumumba, Second World War